2011
DOI: 10.1002/cncr.26193
|View full text |Cite
|
Sign up to set email alerts
|

The Karakiewicz nomogram is the most useful clinical predictor for survival outcomes in patients with localized renal cell carcinoma

Abstract: BACKGROUND: Outcomes after surgical removal of localized renal cell carcinoma (RCC) are variable. There have been multiple prognostic nomograms and risk groups developed for estimation of survival outcomes, with different models in use for evaluating patient eligibility in ongoing trials of adjuvant therapy. The authors aimed to establish the most useful prognostic model for patients with localized RCC to guide trial design, biomarker research, and clinical counseling. METHODS: A total of 390 consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…The model proposed by Leibovich et al (L-score model) [12] was developed for clear cell renal cell carcinomas (CCRCC). Pichler et al attempted to externally validate this model [15], and it has been shown to be superior to the two other integrated staging systems mentioned above [16]. However, the model is now more than 10 years old and was developed based on data for radical nephrectomy from 1970 to 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model proposed by Leibovich et al (L-score model) [12] was developed for clear cell renal cell carcinomas (CCRCC). Pichler et al attempted to externally validate this model [15], and it has been shown to be superior to the two other integrated staging systems mentioned above [16]. However, the model is now more than 10 years old and was developed based on data for radical nephrectomy from 1970 to 2000.…”
Section: Introductionmentioning
confidence: 99%
“…However, the model is now more than 10 years old and was developed based on data for radical nephrectomy from 1970 to 2000. In addition, in the validation studies, the inclusion periods reached relatively far back in time [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…1). 1,4,6,7,9,[14][15][16][17][18][19][20][21][22][23][24] In total, the preoperative Karakiewicz nomogram, postoperative Karakiewicz nomogram, Kattan nomogram, and the Cindolo nomogram were validated in 12 065, 12 868, 6036 and 4045 patients, respectively. In all of the included models, we did not observe any publication bias as assessed by the Begg's and Egger's methods (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9 When applied to external populations in Europe, the original Kattan nomogram has shown variable prognostic accuracy ranging from 61% to 81%. 4,[18][19][20][21]23 In 2007, Karakiewicz and colleagues attempted to improve on the accuracy of the aforementioned models by including more variables that have traditionally been shown to predict survival among patients with RCC. The cohort on which the model was developed included over 2500 patients with various stages of RCC treated at 5 different centres.…”
Section: Cancer-specific Survivalmentioning
confidence: 99%
“…The model relied on patient age, gender, mode of presentation, clinical tumor size, clinical stage of the primary tumor, and presence of distant metastases and showed optimal model discrimination. Since its first external validation performed on a cohort of 1,972 patients [6], only one study further tested the predictive accuracy of this nomogram [7], showing its superiority compared with the other tested nomograms and risk groups in predicting survival outcomes in 390 patients with localized RCC.…”
Section: Introductionmentioning
confidence: 99%